2005
DOI: 10.17221/5598-vetmed
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of optimal conditions for arginase activity in streptozotocin induced diabetic rats

Abstract: The assay conditions needed to achieve maximal activity of liver and kidney arginase in diabetic and non-diabetic rats were investigated and compared. The physicochemical and kinetic properties of liver arginase in diabetic and control rats were very similar, those of kidney arginase were significantly different. It was found that preincubation temperature (68&deg;C), preincubation period (20 min), optimum pH (10.1) of liver arginase and K<sub>m</sub> (3.2) for its substrate, L-arginine, did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…[17] report that the optimum pH of human serum 9.2-9.6. Generally arginases of mammalian are previously show to have basic optimum pH (9.5-10.5) [18] and that is predominantly attributed to that the enzyme active sit composed from basic amino acids [19] . The variance in activity with pH proposes that at the catalytic site an ionisable group may function [7] .…”
Section: Optimum Ph Of Arginasementioning
confidence: 99%
“…[17] report that the optimum pH of human serum 9.2-9.6. Generally arginases of mammalian are previously show to have basic optimum pH (9.5-10.5) [18] and that is predominantly attributed to that the enzyme active sit composed from basic amino acids [19] . The variance in activity with pH proposes that at the catalytic site an ionisable group may function [7] .…”
Section: Optimum Ph Of Arginasementioning
confidence: 99%
“…our results are also compatible with the result of Shatanawi et al(2) who found that arginase activity was elevated in 62 patients with T2DM as compared to age-matched healthy volunteers. Diabetes is accompanied by increased food consumption, amino acid metabolism and ratio of blood glucagon to insulin, all of which would tend to increase the activity of the urea cycle as well as arginase activity (21).…”
Section: Figure 3 Correlation Between Fbs and No In Diabetic Patientsmentioning
confidence: 99%